Integrative Analysis of genetic parameters and traits associated for enhancing Grain yield in Bread Wheat - Anamish Tyagi; Aman Srivastava; Sonali Srivastava; Mallika Jaiswal; Priyansh baliyan; Nitin Kumar; S C Vimal (The Bioscan, 2025)
The present study assessed genetic variability, heritability, and trait associations across ten agronomic traits in a crop breeding population. Analysis of variance revealed significant genetic differences for key traits such as grain yield, spike length, and 1000-grain weight, while block effects were non-significant, confirming experimental reliability. High heritability and genetic advance for grain yield, biological yield, and seed weight indicate strong potential for selection. Correlation and path analysis highlighted positive relationships between grain yield and traits like biomass, tiller number, and seed size, while delayed flowering and maturity negatively affected yield. Principal Component Analysis (PCA) further simplified trait variability, with the first three components explaining over 69% of the total variation, identifying biomass and yield-related traits as major contributors. These results emphasize the importance of early flowering, efficient biomass partitioning, and tillering in yield improvement. The findings offer valuable insights for breeders aiming to enhance productivity through a targeted selection of high-heritability traits.